The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13104-015-1539-4
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin agonists stimulate lipolysis in human adipose tissue explants but not in adipocytes

Abstract: BackgroundThe central melanocortin system is broadly involved in the regulation of mammalian nutrient utilization. However, the function of melanocortin receptors (MCRs) expressed directly in peripheral metabolic tissues is still unclear. The objective of this study was to investigate the lipolytic capacity of MC1-5R in differentiated adipocytes versus intact white adipose tissue.ResultsNon-selective MCR agonist α-MSH, MC5R-selective agonist PG-901 and MC4R-selective agonist LY2112688 significantly stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…BMS-470539 and PG-901 were used as MCR 1 and MCR 5 agonist, respectively, although PG901 also binds with antagonistic activity MC3R and MC4R [20,21]. Compounds were supplied by Professor Grieco (Pharmacy Department, University of Naples Federico II).…”
Section: Methodsmentioning
confidence: 99%
“…BMS-470539 and PG-901 were used as MCR 1 and MCR 5 agonist, respectively, although PG901 also binds with antagonistic activity MC3R and MC4R [20,21]. Compounds were supplied by Professor Grieco (Pharmacy Department, University of Naples Federico II).…”
Section: Methodsmentioning
confidence: 99%
“…The melanocortin 4 receptor (MC4R) gene, located at chromosome 18q21, encodes a G protein-coupled receptor that binds to the α-melanocyte-stimulating hormone. It plays a role in fatty acid metabolism in the liver (promoting lipolysis) and lowering insulin secretion in the pancreas [26]. MC4R is expressed in the hypothalamus in response to the leptin signaling pathways [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…MC4R is expressed in the hypothalamus in response to the leptin signaling pathways [27,28]. It is believed that MC4R induces lipolysis directly in rabbit adipocytes [29] and at a minimum level in subcutaneous adipocytes of obese humans [30], mediated by the intracellular response to neuronal signals [26]. Association signals were identified between MC4R exonic variants and different levels of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Hypercorticosteronemia is also known to result in increased bone resorption and decreased bone deposition [44], and so the elevated corticosterone could potentially explain decreased linear growth of Mc3r -deficient mouse models. A study from Moller et al demonstrated mRNA expression of MC3R in human subcutaneous adipocytes, albiet to a lesser extent than MC1R, MC2R , or MC5R [23]. Additionally You et al showed mRNA expression of Mc3r in rat brain, liver and adipose tissue [45].…”
Section: Introductionmentioning
confidence: 99%